Prevalensi Kuman ESBL (Extended Spectrum Beta Lactamase) dari Material Darah di RSUP Dr. Kariadi Tahun 2004-2005 - Winarto Winarto (MEDIA MEDIKA INDONESIANA, 2009)
Prevalence of Extended-Spectrum  -Lactamases (ESBL)-bacteria of Blood Isolates in Dr. Kariadi Hospital Semarang 2004–2005Background: Prevalence of ESBL bacteria varies among hospitals, which its resistance could be spread to other bacteria; causes infections with a high morbidity and mortality. There were no data of ESBL prevalence and its distribution within Dr. Kariadi hospital wards. Objective of the study were to determine the prevalence, distribution and antibiotic sensitivity pattern of ESBL bacteria in Dr. Kariadi hospital.Methods: Retrospective study was used on laboratory records of in-patients at Clinical Microbiology Laboratory during 2004–2005. Blood culture was inoculated into BACTEC bottle medium, incubated at 370C, isolated, identified and examined for antibiotic susceptibility by Kirby-Bauer method. Inclusion criteria were gram negative bacteria subjected to ESBL screening by cefotaxime, ceftazidime or ceftriaxone disc. Samples without clinical informations were excluded.Results: Four thousand three hundred and fifty blood samples were examined during 2 years periode with culture positive rate was 34.76% consist of gram negative bacteria 59.6% in which ESBL bacteria was 50.6%. ESBL bacteria significantly high recovered from intensive wards. Predominance bacteria were Ps. aeruginosa (50.9%), E. aerogenes (37.5%) and E. coli (8.7%). Sensitivity patterns to meropenem >82.2%, quinolone >65.6% except Ps. aeruginosa 52.5%, fosfomisin >74% except Ps. aeruginosa 15.5%,amikacin >82% except Ps. aeruginosa 20.6%.Conclusions: Bacterial culture positive rate was 34.76% with predominance bacteria was gram negative bacteria (59.6%), in which ESBL detected in 50.6%. The most predominance bacteria were Ps. aeruginosa, E. aerogenes and E. coli. Antibiotic sensitivity patterns mostly sensitive to meropenem, aminoglycocide and quinolone.Keywords: ESBL, intensive wards, meropenem ABSTRAKLatar belakang: Prevalensi kuman ESBL berbeda diberbagai rumah sakit, mempunyai gen penyandi di plasmid yang mudah dipindahkan ke kuman lain dengan morbiditas dan mortalitas tinggi. Di RSUP Dr. Kariadi belum ada data komprehensif tentang prevalensi dan distribusi kuman ESBL. Maksud penelitian untuk memberikan gambaran tentang prevalensi, distribusi dan pola kepekaan kuman ESBL.Metode: Penelitian bersifat retrospektif menggunakan catatan pemeriksaan darah pasien rawat inap yang dikultur menggunakan BACTEC di Laboratorium Mikrobiologi Klinik tahun 2004-2005. Tes kepekaan menggunakan metode Kirby-Bauer. Kriteria inklusi ialah kuman gram negatif yang resisten terhadap salah satu atau lebih dari disk antibiotika cefotaxim, ceftazidime dan cefipim, sedang kriteria eksklusi adalah keterangan klinik yang tidak lengkap.Hasil: Didapat 4.350 sampel, yang tumbuh kuman sebanyak 1.512 (34,76%) terdiri dari kuman gram positif 611 (40,4%) dan kuman gram negatif 901 (59,6%), diantaranya kuman ESBL sebanyak 456 (50,6%). Kuman ESBL di ruang perawatan intensif lebih banyak dibandingkan ruang non-intensif (p=0,00 chi square test). Prevalensinya adalah Ps. aeruginosa (50,9%), E. aerogenes (37,5%), E. coli (8,7%), K. pneumoniae (1,5%), A. baumini (1,1%) dan E. clocae (0,3%). Sensitifitas kuman terhadap antibiotika: meropenem >82,2%, kuinolon >65,6% kecuali Ps. aeruginosa 52,5%, fosfomisin >74% kecuali Ps. aeruginosa 15,5%, amikasin >82% kecuali Ps. aeruginosa 20,6%.Simpulan: Hasil kultur positif 34,76%, kuman ESBL didapatkan 50,9% dengan predominan Ps. aeruginosa, E. aerogenes dan E. coli. Kuman ESBL di ruang perawatan intensif lebih banyak, dengan sensitifitas antibiotika yang masih baik ialah meropenem, aminoglikosida dan kuinolon.